(3TQcGJ GdeSGgeI aj VhA GdbGfhf GdhVYj hGdabg GdGSdGejs - (3Ydi fOje(B, (3GdMeUjs ((3HjQhJ(B:s (3eLO GdeDSSI GdLGeYjI ddOQGSGJ hGdfTQ hGdJhRjY(B,s, 2003)
(3fXGe GdTQcGJ GdeSGgeI aj GdbGfhf GdhVYj,eYGde GdTQcGJ aj GdbGfhf GdhVYj,JfXje GdTQcGJ GdeSGgeI aj GdbGfhf GdhVYj,ChVGY GdTQcGJ GdeSGgeI aj Gdabg GdESdGej,ehba Gdabg GdESdGej ef GdTQcGJ GdeSGgeIs
(3agQS GdBjGJ GdbQBfjI GdcQjeI U(B.313 (3; agQS GdeUGOQ hGdeQGLY U(B.322 (3agQS ddCMGOjK GdTQjaI U(B.314 (3; agQS GdEYdGe U(B.315s
Keywords: (3GdTQcGJ GdeSGgeIs; (3GdTQcGJ(B-(3bhGfjf hJTQjYGJs